Perlindungan Hukum bagi Konsumen pada Bank Beku Operasi - Anak Agung Ngurah Bagus Krisna Pratama; Ni Luh Made Mahendrawati; Ni Made Puspasutari Ujianti (Jurnal Interpretasi Hukum, 2021)
Rapid population growth and current unstable economic growth made it difficult for someone to own a house. Houses in an area are sold by entrepreneurs in cash and credit. Buying housing can be done by crediting banks. On the way the bank was selected to experience bankruptcy resulting in the Bank's Operation Freeze so that the customer was disadvantaged. Research method in this writing uses normative legal research, namely examining problems using a legal basis in the form of statutory regulations and supported by opinions of scholars in the literature. The author in this study discusses two legal issues related to rights and obligations of the parties in the sale and purchase of housing on credit at banks that are declared freeze in operation and settlement efforts if the bank is declared a bank with freeze operations for the customer in buying and selling housing on credit. In this case, customers not yet able to know their rights and obligations as depositors of housing certificate funds at the bank if the bank is frozen in operation and bank that is affected by a freeze operation is also not yet clear on how to resolve if the bank is hit by a freeze operation.